Microstructure and mechanical properties of Mg-14Li-1Al/MWCNTs composites prepared by electrophoretic deposition and accumulative roll bonding. (December 2021) - Xu, Lin; Wang, Jiahao; Wu, Ruizhi; Wang, Jiaxiu; Wu, Huajie; Li, Yang; Hou, Legan; Zhang, Jinghuai
Abstract: Mg-14Li-1Al/MWCNTs composites were prepared by electrophoretic deposition and accumulative roll bonding (ARB). The mechanical properties and microstructure was characterized by tensile test, microhardness, optical microscope and transmission electron microscope. After 6 cycles of ARB, the yield strength, ultimate tensile strength and elongation of the composite are 213 MPa, 266 MPa and 21.6%, respectively. Compared with the as-cast alloy and as-rolled alloy, the yield strength and ultimate tensile strength of the composite were increased by 142.04% and 82.05%, 79.72% and 60.24%, respectively. A highest specific strength of 189 kNm/kg was obtained. The highest microhardness value of the composite is 84.6 HV, which is 66.86% and 49.73% higher than that of the as-cast (50.7 HV) and as-rolled (56.5 HV) alloys. High density dislocations, ultrafine grains, and carbon nanotubes with uniform dispersion were observed in the Mg-14Li-1Al/MWCNTs composites. The strengthening of the composites is mainly contributed to fine grain strengthening and dislocation strengthening.